Alone-together: intergenerational mapping of digital and analogue spaces of self. Issue 3 (3rd July 2022) - Hand, Harriet; Rowsell, Jennifer; Shillitoe, Mark
ABSTRACT: The project featured in this article experiments with mapping methods as part of a research-creation approach to exploring spaces, times, and movements within materialisations of self. Bringing together adults and children across two cities during lockdown, the project problematises a stance on 'learning loss' during the pandemic and instead focuses on the potential of the experiential blurriness of analogue and digital spaces. Rather than seeking to control and structure online learning – thereby denying and limiting its possibilities, explorations, and senses of self – three researchers set out on a speculative approach that acknowledges the dynamic complexity of physical and virtual ways of knowing and being. The article discusses the affordances and challenges that the methodology offers and concludes with the broader implications of this research for reimagined post-pandemic pedagogies. In the end, we advocate for mapping as a way of generously creating spaces and activating meaning-making in diverse learning contexts.